Conquest of Canaan: Israelite Conduct of War according to Biblical Tradition - Malamat, Abraham (1979)
updated version of a paper published in Encyclopedia Judaica, Yearbook 1975-1976 and in Proceedings of Symposia, 1979; p. 39 on Mari.